2358. Acute Flaccid Myelitis Among Hospitalized Children in Texas, 2016. (26th November 2018) - Quick, Rachel; Mcelvain, Dawn; Patel, Bhairav; Murphey, Donald; Bailey, Ann; Fernandez, Marisol; Loftis, Laura; Garcia, Carla; Eger, Lynne; Aguilera, Elizabeth; Wootton, Susan; Castagnini, Luis; et al.
Abstract: Background: This is a multisite study of cases of acute flaccid myelitis (AFM) in Texas during the year 2016 among 6 children's hospitals. AFM is a newly recognized and poorly understood disease. Information related particularly to pathogenesis, treatment, and recovery are lacking. Methods: Children age 0–18 years admitted with AFM defined as acute onset limb weakness with spinal cord lesions on MRI primarily involving gray matter during January 1–December 31, 2016, were reviewed. Abstracted information included demographics, presentation, laboratory findings, treatments, and long-term outcomes up to 18 months after onset of weakness (range 3.5–18 months; median 15 months). Results: 22 patients from 5 hospitals were included. Median age was 4.9 years. Upper extremity involvement was common (77%), with all extremities being involved in 36%. Enterovirus D68 was identified in 3 cases. Other pathogens identified included human parechovirus ( n = 2), human herpesvirus 6 ( n = 1), non-D68 enterovirus ( n = 2), rhinovirus ( n = 1), Mycoplasma pneumoniae (n = 1), Bartonella henselae ( n = 1), and influenza B ( n = 1). In total, 32% recovered fully in strength and function, and 45% had full recovery of function. 18% remain completely dependent on caregivers. All extremities were involved in 8 patients. 6 had significant residual weakness, ranging from flaccidity in one extremity to complete caregiver dependence. One was lost to follow-up after discharge. None of the three patients with Enterovirus D-68 made a full recovery, and all three remain largely dependent on caregivers. Treatments varied, but most commonly included methylprednisolone ( n = 14) or intravenous immunoglobulin (IVIG) ( n = 13). All cases of full recovery were treated with steroids, IVIG, or both. 4 patients were not treated; 2 with eventual recovery of function (Figure 1). Response to IVIG and steroids was variable; no harm was noted in response to IVIG (Figure 2). Conclusion: Our findings overall show more promising outcomes than those seen in the 2014 nationwide outbreak of AFM. Specific treatments were not associated with better outcomes. IVIG appeared to be helpful in several cases and, at the very least, was not harmful. Patients with all extremities involved and/or enterovirus D68 appear to have poorer outcomes. Disclosures: All authors: No reported disclosures.